Edge waves over a shelf - Dolai, P.; Dolai, D.P. (Zielona Góra: Uniwersytet Zielonogórski)
The problem considered in this paper is the derivation of properties of edge waves travelling along a submerged horizontal shelf. The problem is formulated within the framework of the linearized theory of water waves and Havelock expansions of water wave potentials are used in the mathematical analysis to obtain the dispersion relation for edge waves in terms of an integral.
Keywords: shelf; edge waves; Havelock expansion; Galerkin approximation; Gegenbauer polynomial; dispersion relation